2018
DOI: 10.21037/jtd.2018.10.07
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure in cancer: role of checkpoint inhibitors

Abstract: The introduction of immune checkpoint inhibitors have greatly improved clinical outcomes in several cancer types, revolutionizing the management of a wide variety of tumors endowed with poor prognosis. Despite its success, high grade immune related adverse events were observed in patients treated with checkpoint inhibitors. While cardiotoxicity was largely underestimated in initial studies, numerous reports of fulminant myocarditis and fatal heart failure (HF) have been recently described. In this review we di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 97 publications
(106 reference statements)
0
10
0
Order By: Relevance
“…Consequently, the appearance of a new or progressing pericardial effusion may increase the possibility of anti-PD-1/PDL-1-related perimyocarditis but should not be regarded as a separate condition from other findings. In terms of histology, numerous studies indicated that immune checkpoint treatment is accompanied by acute fibrinous pericarditis with mixed inflammatory infiltrations in the pericardial wall and the deposition of surface fibrins [45] .…”
Section: Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the appearance of a new or progressing pericardial effusion may increase the possibility of anti-PD-1/PDL-1-related perimyocarditis but should not be regarded as a separate condition from other findings. In terms of histology, numerous studies indicated that immune checkpoint treatment is accompanied by acute fibrinous pericarditis with mixed inflammatory infiltrations in the pericardial wall and the deposition of surface fibrins [45] .…”
Section: Etiologymentioning
confidence: 99%
“…The presence of dilated cardiopathy without edema (FDG PET/MRI) or with increased troponin markers during treatment with PD-1/PDL-1 inhibitors indicates the existence of non-inflammatory left ventricular dysfunction [47] . One interesting study reported that the reduction of PD-1 expression resulted in dilated cardiomyopathy with severely impaired contraction and congestive heart failure, which resulted in sudden death [45] . PDL-1 expression on cardiomyocytes is upregulated in cardiac diseases such as ischemia–reperfusion injury and left ventricular hypertrophy in preclinical studies [27] .…”
Section: Etiologymentioning
confidence: 99%
“…PD-L1 is expressed on a wide range of non-hematopoietic cells, including murine and human heart [6,8,9], and thus the PD-1/PD-L1 regulatory system is crucial in maintaining peripheral tolerance [10]. PD-1/PD-L1 plays a pivotal role in regulating cytotoxic T-lymphocyte and effector T-helper cell activities to prevent autoimmune myocarditis [11]. Cardiotoxicity can be happening when PD-1/PD-L1 is interrupted.…”
Section: Introductionmentioning
confidence: 99%
“…The patient’s Troponin I levels were 13 times higher than the normal, and myocardial biopsy revealed fibrosis with inflammation infiltrated by CD8+T cells. Myocarditis is also considered to be the earliest cardiotoxic reaction, occurring on average 17 days after initial treatment ( 39 ).…”
Section: Discussionmentioning
confidence: 99%